Design of a Wide-angle Polarization Insensitive Square Ring Hybrid Resonator for Satellite Communication System (IUBAT Review, 2026)
In this paper, a wideband metamaterial absorber (MMA) is proposed based on a resistively loaded square ring resonator. The proposed MMA consists of surface mounted 420 Ω lumped resistors and is designed on a FR-4 substrate. The proposed structure achieved over 90% absorption across a broad frequency range from 23.5 GHz to 28.65 GHz, with a peak absorption of 99.04% at 27.98 GHz having a Shielding effectiveness (SE) of 37.73 dB. The proposed meta-surface absorber shows polarization insensitive characteristics and upholds high absorption across a variety of incident angles. The absorption results achieved by CST studio suite, is further verified using HFSS software and the results are almost identical. The equivalent circuit model desiend by ADS software to check the results and was found closely matched. The proposed design has undergone various simulations such as surface current analysis to check the absorption performance. In addition, Substrate thickness and area are also analyzed using parametric analysis to identify the optimal result. Moreover, the effect of various lumped resistors is also analyzed to understand the absorption mechanism. The proposed absorber covers key parts of the K-band, making the design suitable for satellite and 5G communication systems.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 176-191